Relevance of leukaemia inhibitory factor to anti-melanoma differentiation-associated gene 5 antibody-positive interstitial lung disease - Ichimura, Yuki; Ikei, Hiroyuki; Konishi, Risa; Zeniya, Moko; Okai, Takahiro; Nomura, Toshifumi; Negishi, Kousuke; Okiyama, Naoko (Rheumatology (Oxford, England), 2023)
Abstract Objectives Anti-melanoma differentiation-associated gene 5 (MDA5) antibody-positive rapidly progressive interstitial lung disease (RP-ILD) is a life-threatening disease, the aetiology of which remains unclear. To detect potential diagnostic markers, a transcriptome analysis of the lung sample from a patient with anti-MDA5 antibody-positive RP-ILD was performed. Methods RNA sequencing analyses of an autopsy lung sample from a 74-year-old woman with anti-MDA5 antibody-positive RP-ILD was performed and compared with an age- and sex-matched normal lung sample. Genes with changes of gene expression ≥5-fold were considered differentially expressed genes and analysed by Metascape. The levels of leukaemia inhibitory factor (LIF) were measured in the serum samples from 12 cases of anti-MDA5 antibody-positive ILD, 12 cases of anti-aminoacyl tRNA synthetase (ARS) antibody-positive ILD, 10 cases of anti-transcription intermediary factor 1γ/anti-Mi-2 antibody DM and 12 healthy volunteers. Results Gene ontology enrichment analysis on the RNA sequencing data showed a strong association with antigen binding. Upregulated expressions of IL-1β, IL-6 and LIF were also detected. Serum LIF levels were significantly elevated in anti-MDA5 antibody-positive ILD patients {median 32.4 pg/ml [interquartile range (IQR) 13.2–125.7]} when compared with anti-ARS antibody-positive ILD patients [4.9 pg/ml (IQR 3.1–19.7), P < 0.05] and DM patients [5.3 pg/ml (IQR 3.9–9.7), P < 0.05]. Conclusion Our present study suggested that upregulation of LIF might be a new potential disease marker specific for anti-MDA5 antibody-positive ILD.